Complete genome sequence analysis of Edwardsiella tarda SC002 from hatchlings of Siamese crocodile - Rehman, Muhammad Nafees Ur; Dawar, Farman Ullah; Zeng, Jifeng; Fan, Lixia; Feng, Wei; Wang, Mengqi; Yang, Nuo; Guo, Guiying; Zheng, Jiping (Frontiers in Veterinary Science, 2023)
Edwardsiella tarda is a Gram-negative, facultative anaerobic rod-shaped and the causative agent of systemic disease “Edwardsiellosis”. It is commonly prevalent in aquatic organisms with subsequent economic loss and hence has attracted increasing attention. Here, we investigated the complete genome sequence of a highly virulent isolate “Edwardsiella tarda SC002” isolated from hatchlings of Siamese crocodile. The genome of SC002 was consisted of one circular chromosome of 3,662,469 bp with a 57.29 % G+C content and four novel plasmids. A total of 3734 protein coding genes, 12 genomic islands (GIs), 7 Prophages, 114 interspersed repeat sequences, 248 tandem repeat sequences, a CRISPR component with a total length of 175 pb and ncRNA (tRNA=106, sRNA=37, rRNA=28) were predicted. In addition, the coding genes of assembled genome was successfully annotated against eight general databases (NR=3618/3734, COG=2947/3734, KEGG=3485/3734, Swiss-prot=2787/3734, GO=2648/3734, Pfam=2648/3734, CAZy=130/3734, TCDB=637/3734) and four pathogenicity related databases (ARDB=11/3734, CARD=142/3734, PHI=538/3734, VFDB=315/3734). Pan-genome and comparative genome analysis of the complete sequenced genomes confirmed its evolutionary relationships. Our study confirmed that E. tarda SC002 is a potential pathogen bearing an adequate amount of antibiotic resistance, virulence and pathogenic genes and its open pan-genome may enhance its host range in the future.